2008
DOI: 10.1086/527394
|View full text |Cite
|
Sign up to set email alerts
|

Prior Environmental Contamination Increases the Risk of Acquisition of Vancomycin-Resistant Enterococci

Abstract: We found that prior room contamination, whether measured via environmental cultures or prior room occupancy by VRE-colonized patients, was highly predictive of VRE acquisition. Increased attention to environmental disinfection is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
183
2
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(203 citation statements)
references
References 42 publications
5
183
2
13
Order By: Relevance
“…Furthermore, the capacity of enterococci to survive outside the human body for prolonged periods of time contributes to cross-contamination through the hands of healthcare workers, leading to outbreaks [1,2]. The hospital environment can be a reservoir of resistant bacteria, and the role of a possible dissemination of these bacteria, especially vancomycin-resistant enterococci (VRE) via inanimate surfaces and equipment, has been documented by several researchers [3][4][5][6]. Moreover, the cross-transmission, between patients via contaminated hands and surfaces, of multidrug-resistant microorganisms increases length of stays in hospitals, healthcare costs, and mortality [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the capacity of enterococci to survive outside the human body for prolonged periods of time contributes to cross-contamination through the hands of healthcare workers, leading to outbreaks [1,2]. The hospital environment can be a reservoir of resistant bacteria, and the role of a possible dissemination of these bacteria, especially vancomycin-resistant enterococci (VRE) via inanimate surfaces and equipment, has been documented by several researchers [3][4][5][6]. Moreover, the cross-transmission, between patients via contaminated hands and surfaces, of multidrug-resistant microorganisms increases length of stays in hospitals, healthcare costs, and mortality [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that the presence of a VRE-colonized patient in the previous 2 weeks or a previous positive environmental culture were highly predictive for VRE acquisition by the subsequent occupant of the room 13 . In our study, the majority of the patients (73%) were cared for in just 4 wards and, conversely to the reported literature [14][15][16] , with the exception of the Trauma unit, these wards were not involved in intensive care.…”
Section: Resultsmentioning
confidence: 99%
“…The extent to which such susceptible patients' environments act as a reservoir for infections is contradictory with some authors [3,8,10,16] suggesting that transmission of HCAIs by this route is plausible. Some studies described that the contribution of the environment is negligible [7,9,12,14,18].…”
Section: Introductionmentioning
confidence: 90%